Implementation of the Discovery Learning Model to Enhance Student Learning Independence in IPAS at MIS Nurul Yaqin - Yoga Erdi Saputra; Ika Panggih Wahyuningtyas (International Forum of Researchers and Lecturers, 2025)
This study investigates the implementation of the discovery learning model to enhance the learning independence of Grade V students in the IPAS subject at MIS Nurul Yaqin. The problem arises from limited learning facilities, which reduce opportunities for activities that stimulate creativity, as well as students’ limited ability to recognize and describe shapes and colors in detail. This Classroom Action Research applied the Kemmis and McTaggart model with Grade V students as the research subjects. Data were collected through observation, questionnaires, interviews, and documentation, and analyzed descriptively in both quantitative and qualitative forms. The results show that Discovery Learning effectively improved students’ independence in learning. Through its exploratory approach, students actively engaged in questioning, observing, experimenting, and drawing conclusions in meaningful activities. Improvements were noted in self-confidence, task discipline, initiative in managing learning, motivation to understand material, and responsibility for outcomes. Active participation at each stage—from problem formulation to reflection—enhanced mastery of the properties of light and their applications, while also fostering critical, creative, and responsible learning behavior. Furthermore, the study found that the implementation of Discovery Learning encouraged collaborative interaction among students, allowing them to share ideas, test hypotheses, and provide peer feedback. This created a more student-centered learning atmosphere, shifting the focus from teacher instruction to student exploration. Quantitative results showed that student independence increased significantly, with success rates rising from 47.80% in Cycle I, when learning was still teacher-centered, to 84.76% in Cycle II, as students became more actively engaged both physically and mentally. These findings highlight the importance of using student-centered approaches such as Discovery Learning to develop independence, critical thinking, and motivation. The model not only supported better academic outcomes but also prepared students with essential lifelong learning skills that can be applied across subjects and in real-life problem solving.